Salmonella Carrier State in Ostriches and Epizootological Situation in Ararat Region - Sargsyan, M. A.; Balasanyan, H. S.; Tovmasyan, G. R. (ՀԱԱՀ հիմնադրամ)
Salmonella carrier state of ostriches and epizootological conditions have been studied and identified for the first time in Ararat region of the Republic of Armenia. As an endemic infectious disease, Salmonellosis has caused significant economic damage to ostrich farms. Bacteria carrying birds, caring, feeding and keeping conditions, as well as stressful situations are predisposing factors for the mentioned disease. According to the two-year epizootological investigations, under insecure conditions the indices of infection, death and lethality have made 0.2 (20 %), 0.10 (10 %), 0.53 (53 %) respectively, while the economic loss amounted to 640 000 AMD.
Keywords: Veterinary Science and Animal Breeding